Language evolution and healthiness for critical cyber‐physical systems. Issue 9 (16th September 2020) - Banach, Richard; Zhu, Huibiao
Abstract: In the effort to develop critical cyber‐physical systems, it is tempting to extend existing computing formalisms to include continuous behaviour. This may happen in a way that neglects elements necessary for correctly expressing continuous properties of the mathematics and correct physical properties of the real‐world physical system. A simple language is taken to illustrate these possibilities. Issues and risks latent in this kind of approach are identified and discussed under the umbrella of 'healthiness conditions'. Modifications to the language in the light of the conditions discussed are elaborated, resulting in the language Combined Discrete and Physical Programmes in Parallel (CDPPP). An example air conditioning system is used to illustrate the concepts presented, and it is developed both in the original 'unhealthy' language and in the modified 'healthier' CDPPP. The formal semantics of the improved language is explored.